Quantifying the cardiometabolic burden of increasing BMI: associations with blood pressure, lipids, glucose, insulin resistance, atherogenic dyslipidemia, and metabolic syndrome in Spanish workers - Alberto Ramírez-Gallegos; Margarita Isabel Moyá-Seguí; Mari Carmen Gallegos-Álvarez; Laura López-Velasco; Ignacio Ramírez-Gallegos; Marta Marina Arroyo; Aina Gabriela Valiente-Pizà (Academic Journal of Health Sciences, 2026)
Background: Body mass index (BMI) is widely used to assess obesity-related health risks; however, the magnitude of cardiometabolic deterioration associated with incremental increases in BMI remains insufficiently quantified. This study aimed to evaluate the cardiometabolic burden associated with increasing BMI in a large cohort of Spanish workers. Methods: A cross-sectional study was conducted among 386,924 Spanish workers who underwent routine occupational health examinations between 2019 and 2024. Associations between BMI and cardiometabolic risk markers were assessed using multivariable linear and logistic regression analyses. Outcomes included systolic and diastolic blood pressure, fasting glucose, lipid profile, triglyceride-glucose (TyG) index, atherogenic dyslipidemia, and metabolic syndrome defined according to the NCEP ATP III, IDF, and JIS criteria. Receiver operating characteristic (ROC) analyses were performed to evaluate the discriminatory capacity of BMI. Results: Increasing BMI was associated with progressive deterioration in all cardiometabolic parameters. In fully adjusted models, each 1 kg/m² increase in BMI was associated with increases of 0.85 mmHg in systolic blood pressure, 0.64 mmHg in diastolic blood pressure, 0.36 mg/dL in fasting glucose, and 0.006 units in the TyG index (all p < 0.001). BMI was also independently associated with a higher likelihood of atherogenic dyslipidemia (OR: 1.031; 95% CI: 1.027–1.035) and metabolic syndrome according to ATP III (OR: 1.132; 95% CI: 1.129–1.135), IDF (OR: 1.198; 95% CI: 1.195–1.202), and JIS criteria (OR: 1.156; 95% CI: 1.153–1.159). A pronounced dose–response relationship was observed across BMI categories. BMI demonstrated good discriminatory capacity for identifying metabolic syndrome, with AUC values ranging from 0.797 to 0.843 and optimal thresholds close to 27 kg/m². Conclusions: Increasing BMI is associated with a substantial and progressive cardiometabolic burden characterized by worsening blood pressure, glucose metabolism, insulin resistance, lipid abnormalities, atherogenic dyslipidemia, and metabolic syndrome. Cardiometabolic risk increases across the entire BMI spectrum, highlighting the importance of early prevention and weight-management strategies before obesity becomes established.